1998
DOI: 10.1007/bf01280590
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution electron microscopy on ultrathin sections of cellulose microfibrils generated by glomerulocytes in Polyzoa vesiculiphora

Abstract: Summary. Glomerulocyte cellulosic bundles of Polyzoa vesiculiphora were investigated by microdiffraction and high-resolution electron microscopy. In each bundle, hundreds of cellulose microfibrils, having a rectangular cross-sectional shape, are packed regularly with their 0.6 nm lattice planes parallel to each other. Lattice images reveal that the 0.6 nm plane is parallel to the longer edge of the cross section which is similar to the lattice organization of cellulose with a squarish cross section in Valonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Similar results were obtained for highly crystalline tunicate cellulose, which has pure cellulose I β and a parallelogram cross-section of microfibrils, in layer-by-layer peeling experiments (Figures S4–S6).…”
Section: Resultssupporting
confidence: 81%
“…Similar results were obtained for highly crystalline tunicate cellulose, which has pure cellulose I β and a parallelogram cross-section of microfibrils, in layer-by-layer peeling experiments (Figures S4–S6).…”
Section: Resultssupporting
confidence: 81%
“…In a similar way, no agreement has been reached on the cross-sectional shape of cellulose found from imaging. The cross-section of valonia microfibrils was found to be almost square-shaped with an average size of 180–200 Å (Revol, 1982; Sugiyama et al, 1985) while the cross-section of tunicate cellulose was found to be parallelogram shaped (Helbert et al, 1998a,b). Even though valuable information has been obtained about cellulose microfibrils from electron microscopy, the sample preparation that generally requires drying could introduce artifacts through modifications in the physical structure of native cellulose, such as collapse and aggregation of microfibrils.…”
Section: Cellulose Microfibril Size and Organizationmentioning
confidence: 99%
“…Lattice images of Valonia cellulose microfibrils as well as those of other highly crystalline cellulose samples were soon produced in several laboratories. (Revol, 1985;Tsuji et al, 1985;Brown, 1987a, 1987b;Kuga and Brown, 1989;Chanzy, 1990;Helbert et al, 1998aHelbert et al, , 1998b. The data from electron diffraction diagrams and from images resulting from diffraction contrast have been decisive to reveal the cross-sectional shape of some of the cellulose microfibrils (Nishiyama, 2009).…”
Section: Cellulose With Diffraction Contrast and Low-dose Temmentioning
confidence: 99%